(NsPRAWO^NIK PO WEROQTNOSTNYM RAS^ETAM (B/s - (NtRONX(B, (Na(B.(Np(B.s; (NkOPENKIN(B, (N`(B.(Nn(B.s; (NkOROWINA(B, (Ni(B.(Na(B.s ((NmOSKWA (B:s (NwOENIZDAT(B,s, 1970)
(NbIBLIOGR(B.: (NS(B. 524 - 526s
(NpREDM(B. (NUKAZ(B.: (NS(B. 527 - 530s
Keywords: (NwEROQTNOSTEJ TEORIQs